PENGARUH MODEL MASTERY LEARNING TERHADAP PENGUASAAN KOMPETENSI DASAR MENGAKTUALISASIKAN KEMERDEKAAN MENGEMUKAKAN PENDAPAT SECARA BEBAS DAN BERTANGGUNG JAWAB - Mabrurriyah, Arrum; Al Rasyid, Machmud; ., Wijianto (PKn Progresif, 2016)
This research aimed to find out whether or not there was an effect of mastery learning model on the mastery of basic competency ?actualizing the freedom of expressing opinion independently and responsibly? in the 7th grade of SMP Negeri 14 Surakarta.This study was an experimental quantitative research. The population of research was the 7th graders of SMP Negeri 14 Surakarta in the school year of 2015/2016. The sampling technique used was simple random sampling one. The sample of research consisted of 62 students: 31 in experiment and 31 in control groups. The instruments of collecting data used in this research were questionnaire, observation sheet and documentation. The validation of questionnaire of basic competency ?actualizing the freedom of expressing opinion independently and responsibly? was carried out using validity and reliability test. The validity used was construct validity. Meanwhile, to validate the items of questionnaire, Pearson?s product moment correlational formula was used. Meanwhile, the reliability test used in this study was alpha formula. Technique of analyzing data used was one-predictor regression analysis technique. Considering the result of research conducted, there was a significant effect of Mastery Learning (X) application on the mastery of basic competency ?actualizing the freedom of expressing opinion independently and responsibly? (Y). From the result of data analysis, it could be found rxy value = 0.980 with N = 31 at significance level of 5% and rtable = 0.355. Thus rstatistic (0.980) ? rtable (0.355), so that it could be concluded that there was an effect of X on Y variables. The contribution of Mastery Learning model to the mastery of basic competency ?actualizing the freedom of expressing opinion independently and responsibly? was 91%. Thus, it could be concluded that there was a significant effect of Mastery Learning model application on the mastery of basic competency ?actualizing the freedom of expressing opinion independently and responsibly? in the 7th grade of SMP Negeri 14 Surakarta in the school year of 2015/2016